Analisis Judul Berita pada Surat Kabar Online Harian Rakyat Empat Lawang: (Kajian Semiotika Roland Barthes) - Lesi Kartini; Ummul Khair; Maria Botifar (Institut Agama Islam Negeri Curup, 2024)
AbstractThis research begins with obtaining the meaning contained in signs which are used as objects of study in a scientific research. Sign meanings can use Roland Barthes's semiotic study as a tool for studying objects. Thus the object of study in this study is the news title and its contents in the online newspaper Harian Rakyat Empat Lawang. This study used a qualitative approach with a content analysis research type. Basically when someone reads a newspaper, the reader will see the title first, is there a certain meaning that can be analyzed related to the contents of the news. Thus, the study of semiotics has a role here in order to be able to decipher the meanings contained in the signs in news headlines.This study uses Roland Barthes' semiotics where each title and news content in the online newspaper Harian Rakyat Empat Lawang will be analyzed using Roland Barthes's five semiotic codes consisting of hermeneutic, semimic, symbolic, proaretic, and genomic codes.Â Keywords: semiotics, news headlines, Roland Barthes